2015
DOI: 10.1177/1363461515571624
|View full text |Cite
|
Sign up to set email alerts
|

In or out? Barriers and facilitators to refugee-background young people accessing mental health services

Abstract: Refugee young people are identified as a group with high risk for mental health problems, due to their experience of trauma, forced migration and stressors associated with settlement. A high prevalence of mental health problems is reported in this group, however limited information suggests refugee young people have low rates of mental health service access after settlement, and there is little information on barriers and facilitators to mental service delivery for this group. Using data from 15 focus groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(177 citation statements)
references
References 40 publications
6
162
1
Order By: Relevance
“…Participants suggested that a trusting relationship encouraged patients to share more personal experiences, which helped the GP gather a clearer idea of the patient's experiences and symptoms and identify appropriate treatment options. Trust was presented in one study on refugeebackground young people accessing mental health services as both a challenge and a facilitator (Colucci et al, 2015) and has also been mentioned in similar studies with immigrant patients in a general health context (Priebe et al, 2011;Mirdal et al, 2012;Robertshaw et al, 2017). While our participants discussed trust in a mostly facilitating context, these studies suggest that while the presence of trust can be invaluable, the absence of trust can be detrimental.…”
Section: Summary Of Themessupporting
confidence: 60%
“…Participants suggested that a trusting relationship encouraged patients to share more personal experiences, which helped the GP gather a clearer idea of the patient's experiences and symptoms and identify appropriate treatment options. Trust was presented in one study on refugeebackground young people accessing mental health services as both a challenge and a facilitator (Colucci et al, 2015) and has also been mentioned in similar studies with immigrant patients in a general health context (Priebe et al, 2011;Mirdal et al, 2012;Robertshaw et al, 2017). While our participants discussed trust in a mostly facilitating context, these studies suggest that while the presence of trust can be invaluable, the absence of trust can be detrimental.…”
Section: Summary Of Themessupporting
confidence: 60%
“…Poor mental health literacy, cultural stigma towards mental health or traditional healing beliefs may influence refugee families’ engagement in appropriate therapy and counselling 42. Psychological screening tools may not be culturally appropriate or sensitive, and thus, can fail to identify or underestimate psychological concerns.…”
Section: Resettlement Issuesmentioning
confidence: 99%
“…Relatedly, the importance of considering the particular needs of refugees is important. For example, features of the refugee experience such as torture and trauma can have particular impacts on PHC access and subsequent health outcomes 9,12,16,19,20,[33][34][35][36] and necessitates refugee-specific initiatives, rather than more general migrant programs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, health professionals report increased complexity in working with migrants and refugees, relating to a range of factors including language difficulties and multiple problems reflecting the impact of social determinants that require a multi‐sector response, as well as difficulties for their clients in understanding and navigating different health service entitlements 12,17,18 . Factors associated with improved access to PHC include the availability of appropriate translation and interpreting services, specialist services for survivors of trauma and torture, advocacy services and partnership with migrant and refugee communities 12,19,20 …”
mentioning
confidence: 99%
See 1 more Smart Citation